Welcoming Remarks By Professor Dr. Faisal Rafiq Mahamd Adikan Vice-Chancellor, Universiti Sains Malaysia - Adikan, Faisal Rafiq Mahamd (2020)

(untitled)
Climate change is imminent with severe significant impact on the nation. For Malaysia the rising temperature has had major repercussions, one of which is the rise in sea levels. The recent Asian Development Bank Forum in early 2020 recognized the challenges, and the effect on coastal nations. USM studies pointed out the vulnerability of low lying coastal plains such as that of Kedah, Perak and Selangor, from which our main food resources grow. Here too are the main population areas and cultural heritage sites. There will also be a drastic reduction in coastal fisheries resources as major ecosystems such as coral reefs are obliterated. A rise of 1.5C in ambient sea temperature of more than 2 days will result in coral bleaching which may lead to death – a phenomenon of increasingly common occurrence in the past decades here.